2019
DOI: 10.1002/jcp.28259
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Ras–ERK1/2 signaling promotes the development of uveal melanoma by downregulating H3K14ac

Abstract: Ras–extracellular signal‐regulated protein kinases 1 and 2 (ERK1/2) signaling has been proposed as the crucial regulators in the development of various cancers. Histone acetylation at H3 lysine 14 (H3K14ac) is closely associated with gene expression and DNA damage. However, whether H3K14ac participates in mediating Ras–ERK1/2‐induced cell proliferation and migration in uveal melanoma cells remains unknown. The purpose of this study is to investigate the effect of H3K14ac on Ras–ERK1/2 affected uveal melanoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Furthermore, aberrantly expressed histonemodifying enzymes in UM suggest that histone modifications are involved in this malignancy (Herlihy et al, 2015), which was also well confirmed by recent studies (Y. Li, Sun, Sun, & Yin, 2019). In addition, microRNAs (miRNAs) are another type of epigenetic regulator controlling UM progression.…”
supporting
confidence: 57%
“…Furthermore, aberrantly expressed histonemodifying enzymes in UM suggest that histone modifications are involved in this malignancy (Herlihy et al, 2015), which was also well confirmed by recent studies (Y. Li, Sun, Sun, & Yin, 2019). In addition, microRNAs (miRNAs) are another type of epigenetic regulator controlling UM progression.…”
supporting
confidence: 57%
“…In this study, Ras was found to be an important upstream signaling molecule that upregulates certain genes downstream of the Ras-ERK pathway. These genes, including CYR61, WNT16B, IGFBP3, GDF15, NT5E, and CARD16, are regulators of cancer cell proliferation and migration activity (27). ATF2 is also an epigenetic regulator that possesses intrinsic acetyltransferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…As for histone modifications, both histone acetylation and methylation have a great impact on the development of UM. H3K14ac, an important pattern of histone acetylation, promotes the development of UM through its downregulation [28]. The histone deacetylases (HDACs), which exist in UM tissues extensively, can inhibit the expression of cancer suppressor genes [29].…”
Section: Introductionmentioning
confidence: 99%